Inhibition of Cilia Regeneration of Tetrahymena by Ansamitocins, New Antitumor Antibiotics - Tanida, Seiichi (1979)
Ansamitocins inhibited cilia regeneration of partially deciliated Tetrahymena pyriformis W, and the activity depended on the acyl groups at the C3 position.